Turkey’s role as a regional and global player and its power capacity: Turkey’s engagement with other emerging states - Gürzel, Aylin (Revista de Sociologia e Política, 2014)
Turkey’s role as a regional power has increased since Justice and Development Party (AKP) came to power. AKP leadership not only aspired to become a regional power but also a global player. Turkey has, therefore, assumed different roles: the "natural leader" of the region; a historical "big brother;" and the "protector" of the Muslim minorities. Turkey has also assumed a "mediator" and a "facilitator" role by trying to negotiate a deal with an emerging power such as Brazil in order to attempt to resolve the controversial Iranian nuclear issue. By making use of recent developments, Turkey tried to solidify its long desired role as a "rising power" by increasing its influence in its neighborhood and engaging with other emerging powers. The concept "regional power" is a context-based notion. In other words, the location and geography are contesting and disputed approaches. Notwithstanding the fact that concepts such as "region" and "power" are social constructed reality, this paper analyzes the notion of ’regional power’ as a subcategory of ’power’. In this context, this paper will make use of Stefan Schim’s criteria while analyzing Turkey’s power capacity in the region. Schim posits that the "regional power" needs to have a "role definition," and it should possess material power (hard power). It should also have economic as well as diplomatic and organizational capacity. Its power whether it is ’soft power’ (attraction of ones idea’s and or the ability to set the political agenda in a way that shapes the preferences of other actors) or ’hard power’ (material power that can be measured-economic and military power) needs to be acknowledged by other actors in the region. It should also be accepted by great powers and emerging powers that are determinant in the international system. dditionally, the regional power (and/ or global power) needs to have leverage, thus its power projection needs to yield results. Kalevi Holsti’s role theory will be used as theoretical framework to analyze foreign policy behavior of the AKP. The paper will, thus, seek to find out Turkey’s roles.